Perception And Intention Towards Entrepreneurship By Young Graduates: Case Study In Kuching Division / Fauziah Sharkawi - Haji Sharkawi, Fauziah (2012)
“Promoting entrepreneurship and enterprise creation is high on the policy agenda of almost all countries in the world, as successful enterprises generate additional employment” (Haftendorn & Salzano 2003). “Young entrepreneurs play therefore a fundamental role because they contribute simultaneously to both economic growth and unemployment reduction “ (Schoof, 2006). Today’s youths are an important resource: they are capable of triggering regional innovation processes and technological advances (Frosch 2011), they tend to become more socially active and they are internationally oriented and generally endowed with creativity (Kazmi 1999) and capabilities that allow them to exploit entrepreneurial opportunities. In Malaysia these phenomena is not new, where community involve themselves either directly or indirectly. However, lack of involvement is considered at minimal level. Involvement with entrepreneurship at young age is a part of the alternative to overcome the unemployment among youth. Various agencies giving incentive to youth to encourage and attracted them involve in entrepreneurship. Hence, this study will focus on identifying factors that influenced unemployed graduates involved themselves in entrepreneurship.